2016
DOI: 10.1177/0265813515598991
|View full text |Cite
|
Sign up to set email alerts
|

The connectivity of Haifa urban open space network

Abstract: Urban open spaces are considered as spatial residuals of the expansion of built areas. The environmental impact of the resulting land-cover pattern and associated ecosystem services are frequently evaluated at a crude spatial resolution only. However, wild animals use remaining interconnected fine-grain open spaces as an infrastructure for movement. In this paper, we traced the evolution of an open-space system in Haifa, Israel, and examined the impact of urban morphology on size and distribution of open spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Previous research on OSN has, for example, focused on land‐use regulations to preserve existing ecological networks (Ahern, 2004; Weber & Wolf, 2000), applied landscape ecology models to integrate future vacant lots in shrinking cities (Frazier & Bagchi‐Sen, 2015), investigated energy and resource requirements for scaling‐up urban agriculture (Mohareb et al., 2017), and designed scenarios to reframe circular economy questions through urban and landscape planning strategies (Amenta & Van Timmeren, 2018; Marin & De Meulder, 2018). Another prolific line of research focused on assessing the loss of connectivity among fragmented green patches caused by uncontrolled urban form and urban sprawl (Toger et al., 2016; Yacamán Ochoa et al., 2020). It demonstrated that enhancing connectivity can provide higher social‐ecological values in urban environments (Frazier & Bagchi‐Sen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on OSN has, for example, focused on land‐use regulations to preserve existing ecological networks (Ahern, 2004; Weber & Wolf, 2000), applied landscape ecology models to integrate future vacant lots in shrinking cities (Frazier & Bagchi‐Sen, 2015), investigated energy and resource requirements for scaling‐up urban agriculture (Mohareb et al., 2017), and designed scenarios to reframe circular economy questions through urban and landscape planning strategies (Amenta & Van Timmeren, 2018; Marin & De Meulder, 2018). Another prolific line of research focused on assessing the loss of connectivity among fragmented green patches caused by uncontrolled urban form and urban sprawl (Toger et al., 2016; Yacamán Ochoa et al., 2020). It demonstrated that enhancing connectivity can provide higher social‐ecological values in urban environments (Frazier & Bagchi‐Sen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Large differences in planning practices and climatic and topographic characteristics between, for example, the coastal city of Haifa, situated on a mountain and the coastal city of Tel Aviv lying on the coast, result in different patterns of greenery in the urban cores. [51][52][53] In general, vegetation in residential areas is characterized largely by trees lining streets and gardens interwoven in the built environment, and less by large parks (Figure 1).…”
Section: Study Area Design and Participantsmentioning
confidence: 99%
“…On a local scale, dense urban development may avert the loss of ecological habitats (Conway 2009) but concomitantly increase the barrier effect of built areas (Aguilera et al 2011). Conversely, loose urban development increases landscape fragmentation but the barrier effect of built areas may be reduced if the urban boundary remains comparatively fuzzy (Czamanski et al 2008) and/or if urban patterns are examined at a very fine scale (Toger et al 2016). Maintaining or creating interconnected networks of natural and green areas having various sizes can help to preserve biodiversity.…”
Section: Overview Of Planning Recommendations Classically Advocated To Limit the Negative Effects Of Urban Sprawlmentioning
confidence: 99%